The role of bone marrow microenvironment in platelet production and their implications for the treatment of thrombocytopenic diseases. Issue 10 (26th November 2017) - Wang, Jun-Ying; Ye, Shuang; Zhong, Hua
ABSTRACT: Objectives: Impaired platelet production has been found to be an important pathological mechanism of thrombocytopenia in many diseases. Platelet generation is a complex process that mainly occurs in the bone marrow, and thus is closely regulated by the bone marrow microenvironment. This review attempts to summarize the most current knowledge referring the role of bone marrow microenvironment in the regulation of platelet production. Methods: The effects of multiple microenvironment ingredients in regulating megakaryopoiesis and thrombocytopoiesis have been discussed. Abnormalities of these components in thrombocytopenic diseases are also described. Discussions: Thrombocytopenia is a common clinical manifestation of a variety of diseases. The functional importance of platelets has driven the developments of a broad range of studies. Platelet generation mainly occurs within the bone marrow, where the cells, soluble factors, and extracellular matrix proteins collaboratively form a complex regulatory network, directing megakaryocytic proliferation and differentiation. Alteration in any part of the regulating network may result in defective platelet formation, and eventually lead to thrombocytopenia. A variety of thrombocytopenic diseases have been found to be related with the disregulated bone marrow microenvironment. Identification of the variations of these niche ingredients in certain diseases has facilitated the developments of multiple therapeutic regimes. Further studies that can combine these niche factors with their downstream regulatory factors will be beneficial for developing more effective therapies. Conclusions: Further definition of the role of bone marrow microenvironment in platelet generation may deepen our understanding of the underlying mechanisms as well as provide new therapeutic targets for thrombocytopenic diseases.